Study effect of Fusarium wilt fungus (Fusarium oxysporum f. sp. lycopersici) on biochemical changes on two tomato cultivars - Hadma, M. Salem Abu; Abugharsa, Issa. A.; Saeed, Mohammed A. (Al-Mukhtar Journal of Sciences, 2008)
This study was carried out to determine the effect of tomato infection by Fusarium wilt (Fusarium oxysporum fsp.lycopersici) on two tomato cultivars (Marco & Plaza) on biochemical parameters such as Total soluble sugar and minerals nutrients contents. Most of the nutrients and Total soluble sugar in tested plants of both cultivars were effected by Fusarium wilt infection. Data showed that there were significant differences between inoculated and non-inoculated plants in all biochemical parameters. The rate of Total soluble sugar was decreased in Marco and Plaza by (0.220 and 0.214 mg / g plant tissue) as compared with control (0.293 and 0.338 mg / g plant tissue). Finally the fungal infection caused a significant or remarkable reduction in content of estimated minerals particularly in Nitrogen (2.4 and 5.3 mg / g plant tissue) for Marco and Plaza respectively and potassium (0.48 mg / g plant tissue) for each. Also it caused a sudden decrease in amount of Phosphorus, Magnissium and Calcium and the least amount of Phosphorus was 0.10 mg / g plant tissue (Marco) and 0.05 mg / g plant tissue (Plaza).